Design And Development Of A Broadband Erbium Doped Fiber Amplifiers - Mohemad Kassir, Aiman Mohemad (2003)
This thesis presents the research work that was carried out on the development, characterization and analysis of broadband Erbium doped silica fiber amplifier (B-EDF). Erbium doped fiber amplifiers provide advantages over regenerative repeaters as well as other amplification systems. For example, better crosstalk characteristics, higher power operation, lower insertion loss than semiconductor laser amplifiers, higher efficiency than Raman amplifiers and low noise figure than Brillounamplifiers. In addition, EDFAs are the only amplifier, that can be used as both distributed and lumped amplifier in telecommunications. Currently, optical communication technology is moving from point-to-point systems to optical networking. The exponential growth in data communications and the internet places urgent demands on high-capacity communication networks. To increase the total capacity, amplifier bandwidth has commanded much attention. However, the spread and expansion of dense wavelength division multiplexing (DWDM) systems are keeping pace with various technology developments of optical amplifiers and, in particular, the bandwidth broadening of EDFAs. For this thesis, a novel EDFA structure is developed to increase the amplifier bandwidth by combining the conventional band and long wavelength band (C+L). This will offer more efficient use of optical fiber networks and it will satisfy the demand of higher transmission capacity.